Efficient Cyclic Primes: Efficient Prime Numbers Generate a Cyclic Group of Prime-Order - Tuncer, Turker; Baygin, Mehmet; Tasci, Burak; Dogan, Sengul (Scipedia S L, 2026)
In the realm of mathematics and digital communication, cyclic groups of prime order have emerged as both a foundational and transformative concept. Historically, prime numbers have been pivotal in underpinning numerous cryptographic systems, with their unique properties making them integral for robust security mechanisms. Our in-depth research introduces the novel concept of Efficient Cyclic Primes, a specific subset of primes that demonstrate a heightened capability to generate diverse cyclic groups. Notably, certain prime numbers inherently foster a richer array of cyclic groups compared to others. The genesis and understanding of these efficient cyclic primes are intricately linked to the Euler number, further combined with the base number essential for cyclic group generation. We have proposed a new prime calculation algorithm that not only elucidates the process of identifying efficient cyclic primes but also lists the first 250 efficient cyclic primes that have been computed. By leveraging these primes, we chart a promising trajectory toward conceiving more potent, advanced cryptographic methodologies for the future.
Keywords: Efficient cyclic primes; prime numbers; prime order; cyclic groups; cryptology